Long-term efficacy and reduced side-effects of buprenorphine in patients with moderate and severe chronic pain - Papa, Alfonso; Salzano, Anna Maria; Di Dato, Maria Teresa; Desiderio, Vincenzo; Buonavolontà, Pietro; Mango, Pietro; Saracco, Elisabetta; Tammaro, Dario; Luongo, Livio; Maione, Sabatino (Frontiers in Pharmacology, 2024)
Background: Chronic pain significantly impacts quality of life and poses substantial public health challenges. Buprenorphine, a synthetic analog of thebaine, is recognized for its potential in managing moderate to severe chronic pain with fewer side effects and a lower incidence of tolerance compared to traditional opioids.Objective: This retrospective study aimed to assess the long-term efficacy and safety of buprenorphine transdermal patches in patients with moderate and severe chronic pain, with a focus on pain relief sustainability and tolerance development.Methods: This retrospective observational study involved 246 patients prescribed buprenorphine transdermal patches. We evaluated changes in pain intensity using the Numeric Rating Scale (NRS), assessed opioid tolerance based on FDA guidelines for morphine-equivalent doses, and measured patient-reported outcomes through the Patients' Global Impression of Change (PGIC). Any adverse events were also recorded.Results: Over the 36-month period, there was a significant reduction in NRS scores for both moderate and severe pain patients, demonstrating buprenorphine's sustained analgesic effect. Tolerance measurement indicated that no patients required increases in morphine-equivalent doses that would meet or exceed the FDA's threshold for opioid tolerance (60 mg/day of morphine or equivalent). Additionally, patient satisfaction was high, with the PGIC reflecting significant improvements in pain management and overall well-being. The side effects were minimal, with skin reactions and nausea being the most commonly reported but manageable adverse events.The study findings validate the long-term use of buprenorphine transdermal patches as an effective and safe option for chronic pain management, maintaining efficacy without significant tolerance development. These results support the continued and expanded use of buprenorphine in clinical settings, emphasizing its role in reducing the burdens of chronic pain and opioid-related side effects. Further research is encouraged to refine pain management protocols and explore buprenorphine's full potential in diverse patient populations..